Effectiveness of Halal Traceability and Self-Declared Certification on Indonesian MSMEs Performance - Sadiyah, Siti; Erawati, Emi (Universitas Muhammadiyah Surakarta, 2024)
This study aims to examine in depth the effectiveness of halal tracea-bility in Indonesia and identify the impact of self-declared halal certifi-cation on the performance of small and medium-sized enterprises (SMEs) in the country. The research method used is qualitative, which is reinforced by statistical analysis through survey data from the Popu-lix application as well as a comprehensive literature review. Data anal-ysis was conducted through various techniques, including regression tests, correlation tests, chi-square tests, and content analysis. The re-search findings confirm that the effectiveness of the halal tracking sys-tem significantly contributes to improving the resilience and competi-tiveness of MSMEs. Moreover, self-declared halal certification has been proven to increase consumer confidence in halal products and their integrity. This research makes an important contribution by high-lighting the urgency of integrating efficient halal supply chain man-agement practices, including reliable tracking systems and credible cer-tification. Furthermore, this research underscores the necessity of en-hancing consumer awareness of halal products, thereby facilitating in-formed purchasing decisions and fostering the growth of a more resili-ent halal ecosystem in Indonesia.